Un/Seeing Campus Carry: Experiencing Gun Culture in Texas - Benita Heiskanen (European Journal of American Studies)
This article explores everyday experiences and visual-spatial expressions related to the implementation of SB 11, the Texas Senate Bill that allows “License to Carry” (LTC) holders to bring guns onto public university campuses. In particular, it considers the ways in which members of The University of Texas at Austin community delineate their visual-spatial surroundings and sensory perceptions on campus before and after the implementation of the Campus Carry law. It considers a range of visual interventions by lawmakers and university administrators, as well as counter-visuals created by grassroots activists, faculty, and students. Moreover, it discusses the various ways in which policies are drafted to suppress awareness of firearms from the visual topography of campus space. Drawing on Jacques Rancière’s work on the political dimension of aesthetics, the research presents Campus Carry as an example of a particular aesthetic-political regime created by state legislators and negotiated by the university community. The article demonstrates a tension between seeing and unseeing—remembering and forgetting—the armed campus space and the range of visual metaphors through which firearms are discussed without ever exhibiting the actual, physical object of a gun. The focus on lived experiences that explicate the ramifications of the Campus Carry legislation in Texas contributes an important case for broader analysis of U.S. gun politics and senses of security and insecurity within educational establishments.